Asynchronous Online Community Engagement for Developing Intensive Reading Skills Using a Prototype LMS and Adapted Literary Texts - Dedi Rahman Nur; Arbain Arbain; Godefridus Bali Geroda; Hanita Hanita; Sukaena Sukaena; Akhmad Heriyadi; Indah Farma Pasaribu; Maria Goretti Adella Kornelia Yulianti Hiping; Yasmin Auliasari; Annisa Rohmah (Abdimas Pedagogi: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This community service initiative investigated the implementation of an asynchronous Learning Management System to enhance intensive reading abilities in English language learners. The platform, available at https://publicmodul.my.canva.site/checkreading1 , was developed as a prototype Learning Management System (LMS) to evaluate instructional viability, learner engagement, and the effectiveness of modular delivery in a flexible online setting. The program took place from January 2026 and was structured into six consecutive modules addressing skimming, scanning, primary concept identification, cohesiveness, inference, and tone analysis. Participants engaged in self-directed learning activities, contributed to asynchronous discussion forums, and assembled documentation of their progress via organized reading portfolios. The evaluation utilized LMS activity logs, task completion trends, and qualitative reflections submitted by participants during the training. The results indicate a progressive transformation in reading habits. Numerous learners seemed to diminish word-by-word processing and commenced utilizing more deliberate tactics, especially in skimming and scanning activities. Enhancements in cohesion awareness were also seen in subsequent entries. Inference and tone interpretation continued to be challenging, while portfolio entries suggest developing progress backed by textual rationale. The LMS operated dependably as a prototype for pilot use, although it exposed multiple opportunities for usability enhancement. The results suggest that an asynchronous, community-focused paradigm demonstrates potential for facilitating flexible reading development, while specific enhancements are necessary prior to broader implementation.